Implementation of Organizational Communication at Madrasah Aliyah Plus Taruna Teknik Al Jabbar Medan in Enhancing Teacher Performance - Nasution, Toni; Mesiono, Mesiono; Annisa, Raudatun; Fuadi, Wan Anwar; Siagian, Indra Sakti (LPPPI Publishing, 2024)
The study aims to analyze the implementation of organizational communication at Madrasah Aliyah Plus Taruna Teknik Al Jabbar Medan and its impact on improving teacher performance. This research employs a descriptive qualitative approach with the main informants being the head of the madrasah and the teachers. Data were collected through interviews, observations, and documentation, and then analyzed through data reduction, data presentation, and conclusion drawing, using triangulation techniques to ensure validity by comparing data collection methods. The results show that the head of the madrasah employs various communication strategies, including personal approaches, regular meetings, the use of digital media, and awarding high-performing teachers. However, obstacles such as differing perceptions, language limitations, and suboptimal use of communication media were identified. In conclusion, effective communication has been shown to improve teacher performance, and communication barriers can be addressed with structured strategies and appropriate media utilization.